Psychological capital and music performance anxiety: the mediating role of self-esteem and flow experience - Jiang, Xin; Tong, Yanli (Frontiers in Psychology, 2024)
Background This study aimed to explore the correlation between psychological capital and music performance anxiety among Chinese college students majoring in music. Additionally, the study evaluated the chain mediating effects of self-esteem and flow experience. Methods Three hundred twenty-nine college students pursuing a music major from institutions in Eastern China participated in the study. They were asked to complete the Psychological Capital, Self-Esteem, Flow Experience, and Music Performance Anxiety Scales. Descriptive statistics and correlation analysis were performed, and sophisticated mediation models were created. Results The results suggest that self-esteem and flow experience play a role in connecting psychological capital and music performance anxiety. Moreover, the ultimate model elucidates significant connections linking psychological capital to self-esteem and flow experience in music performance anxiety. Conclusion This study offers useful insights for future interventions aimed at mitigating music performance anxiety through the cultivation of students’ psychological capital, self-esteem, and flow experiences.